Hubungan antara Penggunaan Media Sosial dengan Tingkat FoMO pada Pelajar - Zaki Zahran Safhana; Ratri Rizki Kusumalestari (UNISBA Press, 2024)
Abstract. In this technology-driven era, smartphones and the internet have become essential tools in our daily lives due to their rapid development. The global internet user count currently stands at a staggering 5.16 billion people. While social media is a significant outcome of technological advancements, it also comes with negative impacts such as addiction, which can lead to a fear of missing out (FoMO). This study aims to determine whether there is a relationship between social media use and FoMO levels in students in Bandung. The study used quantitative and correlational methods with a sample of 54 people to determine stratified random sampling respondents. Data collection techniques in this study used questionnaires (questionnaires). The data analysis technique in this study used pearson correlation. The validity test in this study used bivarie pearson and reliability test in this study using Cronbach's alpha formula and correlational test using bivarie pearson. The results of this study There is a moderate relationship between aspect of attention and the level of fear of missing out (FoMO). There is a moderate relationship between the aspect of appreciation and the level of fear of missing out (FoMO). There is a strong relationship between the duration aspect and the level of fear of missing out (FoMO). There is a very strong between the frequency aspect and the level of fear of missing out (FoMO). Abstrak. Dalam era yang sudah didominasi oleh teknologi, penggunaan smartphone dan internet menjadi tak terhindarkan. Saat ini pengguna internet global mencapai 5.16 miliar orang. Media sosial juga merupakan hasil dari perkembangan teknologi, namun tentunya ada dampak negatif dari media sosial, salah satunya yaitu menjadi kecanduan media sosial yang sering kali menciptakan perasaan takut akan ketinggalan (FoMO). Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara penggunaan media sosial dengan tingkat FoMO pada pelajar di kota Bandung. Penelitian ini menggunakan metode kuantitatif dengan metode korelasional dengan jumlah 54 orang dengan penentuan responden stratified random sampling. Teknik data pada penelitian ini menggunakan korelasi pearson. Uji validitas pada penelitian menggunakan bivarie person dan Uji reliabilitas pada penelitian ini menggunakan rumus alpha cronbach dan uji korelasional menggunakan bivarie pearson. Hasil dari penelitian ini terdapat hubungan dengan kategori sedang antara aspek perhatian dengan tingkat fear of missing out (FoMO). Terdapat hubungan dengan kategori sedang antara aspek penghayatan dengan tingkat fear of missing out (FoMO). Terdapat hubungan dengan kategori kuat antara aspek durasi dengan tingkat fear of missing out (FoMO). Terdapat hubungan dengan kategori sangat kuat dengan tingkat fear of missing out (FoMO).